Application of the Presence/Absence (H₂S) Test Vial for Coliforms Detection in Rural Drinking Water of Nepal - Dhimal, Bimala; Kayastha, Rijan Bhakta; Karmacharya, Biraj Man (NPRC Journal of Multidisciplinary Research, 2025)
Background: Access to safe drinking water remains a significant public health challenges in rural regions of Nepal. This study aimed to assess fecal contamination in drinking water sources across eight rural municipalities (RM) of four districts (Dhankuta, Jajarkot, Morang, and Surkhet), using a cost-effective method for detecting fecal coliform in low-resource settings. Method: A total of 160 water samples from diverse sources were analyzed for fecal coliform contamination using the Coliform Presence/Absence (H₂S) test vial. The samples were incubated for 48 hours at ambient temperatures ranging from 22°C to 44°C. By collecting water samples from the identical sources and locations across pre-monsoon and post-monsoon seasons, we directly measured the impact of seasonal variations on contamination. Results: Coliforms contamination was found to be more prevalent during the pre-monsoon season i.e. 72.5% compared to the post-monsoon (57.5%), indicating seasonal variation in water quality. During the pre-monsoon season, contamination was highest in pipe water (78.3%), followed by household-stored water (77.8%), spring water (73.9%), and tube well (56.2%). Post-monsoon results indicate a reduction in contamination for most sources: tube wells dropped to 42.9%, household-stored water to 50%, and spring water to 63.6%, whereas pipe water decreased slightly to 69.6%. Chi-square analysis revealed a significant association between water source type and coliform contamination in both seasons (p = 0.033), as well as a significant association between season and coliform contamination (p = 0.047), suggesting that contamination levels differ between the pre- and post-monsoon seasons Conclusion: This study demonstrates that the presence/absence (H₂S) test is a reliable, low-cost, and practical tool for detecting fecal contamination in drinking water. Its simplicity, affordability, and proven effectiveness make it particularly well suited for rural and resource limited settings where laboratory infrastructure is scarce. The method’s ease of application supports its use in routine water quality monitoring and makes it especially valuable during high-risk seasons, enabling timely public health interventions and improving community protection. Novelty: This is one of the first studies in Nepal to apply the presence/absence (H₂S) test vial across multiple rural municipalities of four districts and a variety of water sources. It provides new insights into regional and seasonal patterns of contamination and demonstrates the feasibility of using the H₂S test in large-scale, decentralized water quality assessments.